Prioritizing future funding and construction of the planned high-speed rail corridors of China – According to regional structure and urban land development potential indices. (September 2019) - Xu, Wangtu (Ato); Long, Ying; Zhang, Wei
Abstract: This paper proposes two types of indices to prioritize the future funding and construction of the planned high-speed rail (HSR) corridors of China. The first index is the regional structure index that evaluates the performance of an HSR corridor from the perspective of spatial connectivity and accessibility, and it consists of regional structure factors (e.g., corridor length and buffer area) and coverage factors (e.g., the total number of HSR stations, cities, and people within the service domain of the HSR corridor). The second index is the urban land development potential index that assesses an HSR corridor depending on the corridor's potential effect on the promotion of urban land development. Following China's latest national railway network planning proposal, planned HSR corridors are prioritized using these two indices. The rankings obtained according to these two indices are presented and compared in this paper. The prioritization of results is then used to suggest patterns of future funding and construction for China's HSR corridors and, further, to suggest potential implications for HSR planning and development in other countries. Highlights: Two types of indices are used to prioritize HSR corridors. The first index is the regional structure indicator. The second index is the urban land development potential indicator. Funding and construction schedule arrangement of HSR corridors are given out.